ByzRev 06.2024.031: Sergej Pavlovič Karpov, История Таны (Азова) в XIII–XV вв. [History of Tana (Azov) in the XIII–XV centuries].: Vol. I: Тана в ХIII–XIV вв. [Tana in the XIII–XIV centuries] (Новая Византийская библиотека. Исследования). Saint Petersburg: Алетейя 2021. - Quirini-Popławski, Rafał (The Byzantine Review, 2024)
Sergej Pavlovič Karpov, История Таны (Азова) в XIII–XV вв. [History of Tana (Azov) in the XIII–XV centuries]. Vol. I: Тана в ХIII–XIV вв. [Tana in the XIII–XIV centuries] (Новая Византийская библиотека. Исследования). Saint Petersburg: Алетейя 2021. 378 pp., 6 figs. – ISBN 978-5-00165-314-1